Perkembangan Sistem Manufaktur - Enty Nur Hayati (Jurnal Ilmiah Dinamika Teknik, 2008)
Bill of material is a list of amount of component, materials mixture, and needed to raw material make an product Technique Planning Requirement of Material used for the planning and control ofgoods item (depended komponen) at a peg higher item. Out put from calculation of MRP is determination sum up the each BOMB from required item at the same time with date of requiring of JIT represent a pull system which producing last one unit puled to place needing it at the time of needed.